AB1333 Retention rates of adalimumab, etanercept, and infliximab as biotherapies for rheumatoid arthritis, spondyloarthritis, or psoriatic arthritis patients in daily practice in auvergne (FRANCE). (12th June 2018) - Soubrier, M.; Fan, A.; Couderc, M.; Malochet-Guinamand, S.; Mathieu, S.; Giraud, C.; Tournadre, A.; Dubost, J.-J.; Pereira, B.
Abstract : Background: The use of TNF-α inhibitors, has considerably improved the treatment of rheumatoid arthritis (RA), spondyloarthritis (SpA), and psoriatic arthritis (PsA). The most widely used anti-TNFs are infliximab (IFX), adalimumab (ADA), and etanercept (ETN). Their efficacy and safety have been demonstrated in randomised controlled trials, though of short duration and involving a selected patient population differing from those seen in daily practice. Objectives: To compare, in real-life settings, the retention rates of anti-TNF treatments (ETN, ADA, or IFX) initiated as first-line biotherapy following their approval in the three clinical indications. Methods: Monocentre retrospective cohort involving patients on initial anti-TNF therapy for RA, SpA, or PsA since 2006. Results: Anti-TNF treatment was initiated on 228 RA (ETN 160, ADA 45, or IFX 23), 208 SpA (ETN 91, ADA 62, or IFX 55), and 81 PsA (ETN 40, ADA 26, or IFX 15) patients. Treatment retention rates at 1, 3, and 5 years were 82%, 53%, and 44% in PR; 75%, 57%, and 49% in SpA; 75%, 64%, and 51% in PsA, with no differences detected among the pathologies (p=0.96). Retention rates at 1, 3, and 5 years did not differ among the 3 anti-TNFs either for all pathologies included (ETN: 80%, 57%, and 43%; ADA: 80%, 58%, and 51%; IFX 72%, 56%, and 52%; p=0.75) or each pathology alone (RA : ETN: 83%, 55%, and 41%; ADA: 83%, 51%, and 51%; IFX: 76%, 44%, and 44%, p=0.84; SpA : ETN: 78%, 57%, and 48%; ADA: 78%, 59%, and 46%; IFX: 68%, 55%, and 52%, p=0.81; PsA : ETN: 70%, 60%, and 36%; ADA: 79%, 69%, and 69%; IFX: 80%, 66%, and 53%, p=0.65). Overall, 89 RA, 85 SpA, and 28 PsA patients discontinued treatment for inefficacy (32%) or side effects (SE, 9%)). In RA, predictors for treatment discontinuation were: Disease activity (DAS 28 ESR HR: 1.27 [1.05–1.55]; DAS28-CRP HR: 1.27 [1.03–1.60]), (CRP HR: 1.01 [1.01–1.02]), and corticosteroid intake (HR: 2.05 [1.027–3.32]). Concomitant methotrexate intake tended to decrease the treatment discontinuation risk (HR: 0.64 [0.41–1.01)]. Predictors for treatment discontinuation due to inefficacy were similar (DAS28 ESR, HR: 1.31 [1.05–1.63]; DAS28 CRP, HR: 1.33 [1.04–1.72], CRP HR: 1.02 [1.01–1.03]), corticosteroid intake HR: 3.79 [2.02–7.11]). We were unable to identify any predictors for treatment discontinuation due to SE, though corticosteroid intake was found to be protective (HR: 0.23 [0.07–0.71]). In SpA, the sole predictor for treatment discontinuation identified was increased BASDAI score (HR: 1.02 [1.01–1.04]), while the sole predictor for treatment maintenance was inflammatory syndrome (CRP HR: 0.97 [0.95–0.99]. Similar findings were seen for treatment discontinuation due to inefficacy (BASDAI HR: 1.03 [1.01–1.05)]; CRP HR: 0.98 [0.96–0.99]). We were unable to identify any predictors for treatment discontinuation due to SE. In PsA, active smoking was revealed to be a predictor for treatment discontinuation due to inefficacy (HR: 2.234 [1.02–4.91)]. Conclusions: ETN, ADA, and IFX display similar treatment retention rates in RA, SpA, or PsA without between-agent differences. Disclosure of Interest: None declared